Decisional control preference among Chinese patients with advanced kidney disease: the role of mastery, perceived social support and self-efficacy. Issue 10 (26th November 2022) - Gao, Yajing; Shan, Yan; Wang, Shuolin; Li, Xue; Jiang, Tingting; Cai, Li; Jiang, Xinxin; Wang, Hong
ABSTRACT: Although previous studies have shown a correlation between mastery, self-efficacy, and perceived social support among Chinese patients with advanced kidney disease, few studies have examined their relationship pathways. This study aimed to examine decisional control preference and the relationship between mastery, perceived social support, and self-efficacy among patients with advanced chronic kidney disease. A cross-sectional survey was conducted, and 350 participants were investigated using Control Preference Scale, Personal Mastery Scale, Perceived Social Support Scale, and Self-efficacy Scale. The mediating relationships were determined via structural equation modeling. Results showed that education and economic status were demographic factors influencing patients' decisional control preference. The model showed that mastery and self-efficacy had a direct effect on decisional control preference while perceived social support had an indirect effect mediated via mastery and self-efficacy. Therefore, improving self-efficacy can increase patient willingness to involve in medical decision-making. This study provides new interventions and future directions for promoting decisional control preference.